A strain energy density criterion for the initiation of edge debonding. (October 2015) - Martin, Eric; Leguillon, Dominique
Highlights: Initiation of edge debonding is analyzed within a bimaterial specimen. A coupled criterion and a strain energy density criterion are compared. The coupled criterion is helpful to define the radius of the control volume. Abstract: Material or geometrical discontinuities within a structure induce a localized stress concentration which may initiate a crack leading to catastrophic failure in brittle materials. To assess crack initiation in the vicinity of a V-notch, a criterion based on the strain energy density (SED) averaged over a volume surrounding the notch tip is an attractive approach. It is demonstrated that this criterion can also be used to predict crack initiation along an interface. The precise definition of the control volume is obtained with the help of a coupled criterion which relies on finite fracture mechanics.